Measurement of employer attractiveness in the chinese context: an updated analysis of students' perspective - Guéry, Maximilien Michel Robert (2018)
The increasing intensity of international competition among organizations and the elevation of the level of expertise of fresh graduates put employer branding at the heart of today’s preoccupations. The war for talents is real and organizations around the world are looking for the best assets beyond the borders of their own countries. Understand the dimensions and criteria that appeal to possible candidates is an undeniable advantage. This study investigates the dimensions of employer attractiveness that are relevant to Chinese candidates by re-using the model developed by Zhu et al. (2014) and assesses the impact of the gender on the perception of this employer attractiveness. A quantitative study has been used to harvest the results of 121 respondents at Southwestern University of Finance and Economics in Chengdu, China. Significant differences have been found for three of the five dimensions, indicating on a general level, that females rated significantly higher than males the three dimensions. These results are then further discussed and interpreted via a theoretical and a managerial approach.